Effects of microwave power, treatment time and sample orientation on heat distribution in mango - Varith J. (2014)
Quarantine heat treatment to disinfest oriental fruit fly (Dacus dorsalis H.) in mangoes (Mangifera indica L.) is necessary for fruits exported to developed countries. Microwave provides rapid heating in food materials which may shorten the fruit quarantine process. The objectives of this work were to preliminarily assess the heat penetration of the microwave in mango and to determine the optimal condition to obtain a uniform heating in mango. A household 800 watt-microwave oven was used to provide heating on export-graded 'Chokanan' mango (weight of 320 g /fruit). The experiments were conducted to investigate factors including microwave power, heating time, and sample orientation affecting the heat penetration and heat distribution in mango. The internal temperature mapping of the mango was obtained to assess the heat distribution inside the fruit along with thermogram to illustrate its surface temperature. It was found that mango heated with microwave power of 50% for 40 sec yielded the internal temperature of 45°C at 23 mm underneath the skin where the flesh was thickest and susceptible to the slowest heating. With the aforementioned condition, the mango treated with microwave in the transverse position retained better heating uniformity than did in the normal position. Microwave heat treatment on mangoes may offer advantages over the standard vapor heat treatment (VHT) during come-up time, in terms of less energy consumption, easier implementation for a continuous system, and possibly better product quality retention due to shorter come-up heating time.